Scaling Relationships Among Heart Rate, Electrocardiography Parameters, and Body Weight - Cruz Aleixo, Amanda Sarita [UNESP]; Alfonso, Angélica [UNESP]; Oba, Eunice [UNESP]; Ferreira de Souza, Fabiana [UNESP]; Salgueiro Cruz, Raíssa Karolliny [UNESP]; Fillippi, Maurício Gianfrancesco [UNESP]; Chiacchio, Simone Biagio [UNESP]; Tsunemi, Miriam [UNESP]; Gomes Lourenço, Maria Lucia [UNESP] (Elsevier, 2017)
Although heart rate (HR) is one of the most important clinical parameters determined via physical examinations, little information is available on the normal HR in dogs, which may be related to the high variability of body weight (BW) in this species. HR is determined by the discharge rate of the sinus node, which is dependent on the autonomic nervous system and the release of catecholamines. The allometric relationship between BW and HR in different species has been described as inversely proportional; however, this relationship has been refuted. Certain authors have reported that the relationship between HR and BW in dogs is based on temperament as well as sympathetic autonomic stimulation of the sinus node in small breeds compared with large breeds. The aim of this study was to analyze the effects of weight, sex, age and temperament on the HR, heart rate variability and serum catecholamine (epinephrine and norepinephrine) levels in dogs. We evaluated 48 adult dogs of both sexes and various breeds and ages and divided the dogs into 5 BW groups: <5 kg (n = 8), 5-10 kg (n = 10), 10-25 kg (n = 10), 25-45 kg (n = 10), and >45 kg (n = 10). The measured parameters were HR, breath rate (BR) and body temperature. We also performed an ambulatory electrocardiogram and electrocardiography (ECG) test for 24 hours (Holter monitor) and determined the serum levels of the catecholamines epinephrine and norepinephrine. We observed correlations between HR and sex; differences among the weight groups with respect to ECG variables and epinephrine levels; and differences among the temperament categories for certain clinical parameters, such as HR and BR. Age affected the R wave amplitude, and an allometric relationship was not observed between HR and BW in the dogs. Our results indicated that weight was associated with variations in the ECG variables; age and sex were associated with variations in HR; and temperament had a significant influence on the HR and BR of the dogs.
Keywords: allometry; autonomic nervous system; dog; heart rate variability; Holter; temperament